Codicology and dialectal affinity of continuous Apostolus manuscript - A.A. Bakshaeva; O.F. Zholobov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper considers for the first time the codicological characteristics and dialect features of the handwritten Old Russian so-called Tolstovskii Apostolus. It has been established that the codex has a unique composition for the Old Russian writing, representing the full version of the text of the Preslav recension. An online edition of the manuscript was created at Kazan Federal University. This is a machine-readable publication that is accompanied online by search modules and various pointers. It is posted on the “Manuscript” portal in the “Kazan Electronic Collection”. The study of the manuscript has been performed with the help of electronic technology in the framework of the new direction in the humanities – digital humanities. Recently, a hypothesis of the same provenance of this Apostolus and the Onega Psalter (precisely dated by 1395) has emerged. Besides, it is assumed that both manuscripts were produced at a Moscow scriptorium. The paper critically examines these hypotheses describing the manuscripts’ history and comparing their handwritings, orthographic systems, and decoration. The study presents for the first time the results of the analysis of the regional peculiarities of the Apostolus’ manuscript, which confirm its northwestern origin and organic connection with the book culture of northwestern Russia in the mid-14th century. Thus, the analysis of the codicological characteristics and the linguistic features, including the dialectal parameters of these codices, has confirmed significant discrepancies in the history of the creation and existence of the Tolstovskii Apostolus and the Onega Psalter.